International Production and Wage Coordination in an Integrated Economy (revised) - Domenico Buccella (FIW - Research Centre International Economics, 2011)
Key aspects in economic integrated areas like the EU are both the internationalization of productive activities, which usually occurs in unionized countries, and the ongoing process of labor market integration. In a symmetric two-country duopoly model with integrated product markets, this paper investigates the incentives for unions to coordinate wage demands in the presence of transaction costs. It shows that, contrary to conventional wisdom, under certain conditions wage coordination could lead from a social point of view to a Pareto superior outcome respect to separate wage settings.
Keywords: F21; F23; J50; J51; 330; international production; wage coordination; labor unions